INTER-CHARACTER ASSOCIATIONS IN EVOLVED AROMATIC RICE GENOTYPES - VIR, OM; SINGH, B.B. (Annals of Agricultural Research, 2014)
Thirty advanced, evolved aromatic rice genotypes were evaluated over two years to find out the nature and magnitude of inter character associations. In general genotypic correlation coefficients were higher than their phenotypic counterparts. Phenotypic correlation coefficients were estimated to be positive and significant of biological yield per plant, harvest index, No. of fertile tillers per plant, No. of fertile spikelets per plant, panicle length (cm), panicle weight 1000-grain weight (g), days to 50% flowering, reproductive period (days) and days to maturity with grain yield per plant (g). All these characters also manifested positive and larger direct effects on grain yield . Therefore, practicing selection in segregating generations for these characters may be useful in elevation of yield level in aromatic rices.